Problematising pedagogical action research in formal teaching courses and academic development: a collaborative autoethnography. Issue 2 (15th March 2021) - Arnold, Lydia; Norton, Lin
ABSTRACT: In this paper, we explore action research as a method of academic development. Our focus is specifically on formal taught programmes such as PGCerts, MAs and doctoral studies as well as CPD workshops. In our dual roles as action researchers and academic developers, we had independently noticed that the type of action research that often featured as an assessed component of taught programmes held characteristics which differed from the approach that we knew and had practised. We had worked together as colleagues for several years and as our professional relationship grew so did our combined understanding of pedagogical action research (PedAR) – a form of action research that focuses on learning and teaching in higher education. Collaborative autoethnography helped us to problematize and surface the difficult tensions and dilemmas in our academic development practice. As part of the process we tried to hear our own internal voices which highlighted doubts, frustrations, contradictions, and sometimes joy. We also used the dialogue to step back and consider what else may be going on 'out there' to explain the emergence of particular types of PedAR. We analysed an ongoing, semi-structured, deliberately critical emailed conversation in which we shared experiences and observations to answer our research question 'How do our own experiences inform a critique of the use of PedAR in academic development in higher education?'